2019
DOI: 10.35943/mvmj.2019.23.203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cadmium and /or Chromium on reproductive organs and semen profiles of male albino rats

Abstract: Objective: To evaluate the potential hazards of cadmium and/or chromium on the reproductive system of adult male albino rat. Design: Randomized controlled study. Animals: Forty mature male albino rats weighing 260 ± 10 g. Procedures: Rats were allocated into four groups (ten animals each). Control group (group 1), group 2 received 4.4 mg kg-1 cadmium chloride, group 3 was given 2.5 mg kg-1 sodium dichromate and group 4 received combination of Cd (2.2 mg kg-1) and Cr (1.25mg kg-1) orally, once daily for 65 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…29 Eman et al states that the higher BMI is one of the risk factors for abnormal semen parameters. 30 In this study found that obese oligozoospermia group shows abnormal LH level compared to normal group. This study shows a negative correlation of LH with sperm count (r=-0.41, p<0.05), motility (r=-043, p<0.05) and morphology (r=-0.04, p<0.05), which supports our findings.…”
Section: Discussionmentioning
confidence: 60%
“…29 Eman et al states that the higher BMI is one of the risk factors for abnormal semen parameters. 30 In this study found that obese oligozoospermia group shows abnormal LH level compared to normal group. This study shows a negative correlation of LH with sperm count (r=-0.41, p<0.05), motility (r=-043, p<0.05) and morphology (r=-0.04, p<0.05), which supports our findings.…”
Section: Discussionmentioning
confidence: 60%
“…The respective non significant and increasing influences reported in these two observations may be partly due to the species difference. Semen analysis of rats in sub chronic exposure to Cr was equally reported to result in a significant decrease in total sperm count and viability with a significant increase in the percent of sperms with abnormal morphology (Abd Elhafeez et al, 2019). In another study, the relative weight of testis, the number of epididymal spermatozoa and sperm motility were reportedly reduced in chromium treated rats (Marouani et al, 2012).…”
Section: Semen Characteristics Of Cocks Fed Crpic-treated Diets With ...mentioning
confidence: 96%
“…The significant reduction in the parameters weights at high dose could be the result of structural damage. In another development, exposure to Cr was reported to cause a reduction in weights of testes, epididymis, seminal vesicle and prostate glands (Abd Elhafeez, Halawa, Hamed, & Abouelmaged, 2019). The testes being the site of spermatogenesis are very sensitive to Cr.…”
Section: Epididymal and Testicular Characteristics Of Cocks Fed Crpic...mentioning
confidence: 99%